Oral Submucosal Fibrosis-Early Diagnosis; A Key to Successful Management - Dileep Kumar, Aneel Kapoor, M. lmran Rathore (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2016)
Objective: To diagnose the cases of oral submucosal fibrosis in early stage in out patients department. Study design: Descriptive study. Place & Duration: Department of ENT, Muhammad Medical College and hospital Mirpurkhas, Pakistan from Jan 2013 to Dec 2014. Material & methods: A total of 256 patients were registered through non-probability purposive technique in the outpatient department. Biopsy of all those patients was taken and checked if any of those patients has already developed malignancy, and in that case that patient was excluded from the study. Results: Out of 256 patients which we registered, 170 patients were male and 86 were female. The age range was 7 years to 48 years. The burning sensation was the primary complaint in 86% of the patients. Restricted oral cavity opening was the chief complaint in 55% of the patients. Dysphagia was present in 60% and dryness ofmouth was present in 67%. Conclusion: Oral submucosal fibrosis (OSF) should be diagnosed as soon as possible so as early management can be done. It is seen that the prognosis of OSF depends upon the severity of disease at presentation. Greater the stage of disease the poorer the prognosis